Poisson's Ratio and Modulus of Gyroid Lattices. Issue 12 (27th July 2021) - DeValk, Tyler; Lakes, Roderic
Abstract : Gyroid surface lattices of different densities exhibit Young's modulus consistent with stretch‐dominated extremal behavior approaching the Hashin–Shtrikman upper bound. The gyroid lattices exhibit a Poisson's ratio of 0.34 ± 0.06 independent of direction, independent of specimen diameter, and independent of chirality. This behavior is in contrast with prior chiral lattices that exhibited pronounced size effects in Poisson's ratio, allowable for chiral elastic solids. Abstract : Gyroid lattices (shell lattices with cubic structural symmetry) exhibit a density dependence of Young's modulus consistent with stretch‐dominated behavior. The modulus is extremal and approaches the Hashin–Shtrikman upper bound. The Poisson's ratio exhibits no significant dependence on direction, chirality, or specimen size. This behavior is in contrast with prior chiral lattices that exhibited pronounced size effects in Poisson's ratio.